P-100 Work Disability Due to Inflammatory Bowel Disease: Evaluation of Social Security Benefits in Brazil. (February 2017) - Oliveira-Silva, Christien; Zaltman, Cyrla; Costa, Marcia; Moreira, Jessica
Abstract : Background: Inflammatory bowel disease (IBD) is characterized by a chronic disease with relapsing and remission periods. Intestinal and extraintestinal manifestations can impact on career and work life. The aim of this study is to evaluate the incidence of disability pension and early retirement granted by Brazilian Social Security due to IBD and identify the profile of beneficiaries between 2003 and 2014. Methods: Cross-sectional, descriptive and quantitative study. Data about benefits granted between 2003 and 2014 were collected through the request to Electronic System Citizen Information Services (e-SIC) and inquiry to database of Social Security by AEPS InfoLogo. Variables analyzed were: ICD-10 (K50 and K51 and their variants, excluding K51.4); kind of benefit; sex; date of birth; benefit requirement date; start receiving benefit date; date of disease onset; date of disability onset; salary range and geographic region. Data collected were distributed in Excel (Microsoft Office 2013) and analyzed using SPSS for Windows 10. Results: From June 2003 to December 2014, 25, 319 benefits were granted for IBD patients and 23, 525 (92.9%) were related to disability pension. K51 and its variants (UC) predominated with 14, 775 (58.4%) benefits. There were 917 (51.1%) early retirements due K50 and its variants (CD). And 13, 898 (59.1%) disability pensions were due K51 and its variants (UC). Eleven thousand nine hundred twenty-one (47.1%) benefits were for taxpayers who received <1 minimum wage. Eighty-one percent of benefits were granted to southeast (14, 744/58%) and south (5855/23%) workers. Average age at start receiving disability pension was 38.5 (±10.7) years old and 46.5 (±9.9) years old at begin receiving early retirement. Stratifying for ICD, the average age at start receiving benefits was 37.8 (±10.7) for CD and 40 (±11) years old for UC. Average age for disease onset and the disability onset were, respectively, 35 (±11.1) and 38.3 (±10.7) years for disability pension and 40 (±11.4) and 43.4 (±10.5) years old for early retirement. Stratifying for ICD, average age at disease and disability onset were respectively, 33.3 (±11) and 37.4 (±10.6) for CD and 36.6 (±11.1) and 39.6 (±10.8) for UC. Concerning time between disease onset and benefit requirement date, UC disabled workers took an average of 1180.8 (±1696.4) days while CD ones took 1609.5 (±2083.7) days. Additionally, from 2008 to 2014, among early retirement benefits, 1, 307, 481 were granted, which 11, 108 (0.85%) due to diseases of the digestive system and 976 (8.78%) by ICD K50, K51 and their variants. Conclusions: Benefits granted predominated on most developed regions of Brazil and mainly for UC and low-income taxpayers. Average age at start receiving benefits was between third and fourth decades of life, an important productive age group. The most granted benefit was the disability pension, but early retirement predominated in CD and its variants. Average time between disease onset and incapacity onset was less than 4 years. Although disease and disability onset were earlier among CD, benefit requirement was later than in UC. IBD was important factor on early retirement.